SAFT‐γ Mie model for ionic liquids. Issue 6 (4th April 2022) - Dong, Yichun; Warsahartana, Hubertus Gilbert; Hammad, Faisal; Masters, Andrew
Abstract: The SAFT‐γ Mie model is a recent version of statistical associating fluid theory (SAFT), which uses a group contribution approach to obtain a high‐quality equation of state. In this work, this model is, for the first time, extended to ionic liquids (ILs). The SAFT‐γ Mie calculated values agree well with the experimental data for one‐component, binary and ternary systems that contain ILs, thus indicating the versatility and accuracy of this extension.